AUTOMATIC ROLLING PICTURE DESIGN FOR LEARNING MEDIA FOR DEAF KINDERGARTEN SLB STUDENTS KARYA MULIA SURABAYA - Widi Sarinastiti; Dwi Susanto; Novita Astin; Nina Kurniasari; Umi Rotul Marwiyah (Ide dan Dialog Desain Indonesia (Idealog), 2022)
Deafness is an experience of reduced listening ability that makes people unable to perceive stimuli through the sense of hearing. Deafness will have an impact on the education received by the suf erer. When communicating, the language used in daily life is sign language. One of the provinces with the most deaf people in Indonesia is East Java.. SLB Tunarungu Karya Mulia kindergarten of Surabaya is one of the schools specializing in hearing impaired people. This kindergarten has a learning media in the form of Rolling Picture that works manually. This makes the learning process less ef icient. With this, it is necessary to develop a Rolling Picture that can be moved automatically using a remote. Automatic Rolling Picture contains 9 meters long material with a weight of 4,160 grams and can be controlled with remote using two buttons. When the first button (previous) is pressed, the motor will move CW (Clockwise) that is clockwise, to run the next material, and the button (next) then the motor will move CCW (Counterclockwise) which is counterclockwise to change the previous material. The use of remote can control the tool with a maximum distance of 5 meters. It is expected that this learning media can facilitate teachers to teach and facilitate students in learning sign language vocabulary. Keyword : deaf, learning media, automatic rolling picture design, vocabulary poster design